Relationship between self-efficacy and university dropout: a systematic review - Bernardo, Ana B.; García-Gutiérrez, Vanesa; Esteban, Maria; Maluenda-Albornoz, Jorge (Frontiers in Psychology, 2025)
Self-efficacy is a key determinant of university student persistence, while dropout remains a global challenge. This article is a systematic review of a large body of research examining the relationship between self-efficacy and university dropout. A literature search was started in databases, eligible studies were selected according to inclusion and exclusion criteria and their quality was analyzed, obtaining the 16 documents that were finally analyzed. The results show that the phenomenon of abandonment and the understanding of the different related variables is considered a problem of growing interest in the scientific community. Self-efficacy is a key factor in students continuing their studies. Students with higher self-efficacy are less likely to drop out of university. However, most research in the field is cross-sectional, which limits the understanding of how self-efficacy changes over time. More longitudinal research is suggested to address this limitation and to develop educational policies that strengthen self-efficacy and reduce dropout.